Bone mineral density and degenerative changes of the lumbar spine in former elite athletes - Schmitt, H.; Friebe, C.; Schneider, S.; Sabo, D. (International Journal of Sports Medicine, 2005)
The aim of this study was to assess bone mineral density (BMD) and degenerative changes in the lumbar spine in male former elite athletes participating in different track and field disciplines and to determine the influence of body composition and degenerative changes on BMD. One hundred and fifty-nine former male elite athletes (40 throwers, 97 jumpers, 22 endurance athletes) were studied. Anthropometric (age, body mass index [BMI]) and sport-specific data (personal best, intensity, duration, and time since termination of competitive sports career as well as current sporting activity) were collected. Degenerative changes of the lumbar spine in lateral view were evaluated by using the Kellgren and Lawrence Score. Bone mineral density of the lumbar spine was measured in an anterior-posterior view with dual energy X-ray absorptiometry (DEXA, T-score). Throwers had a higher body mass index than jumpers and endurance athletes. Throwers and jumpers had higher BMD (T-LWS) than endurance athletes. Bivariate analysis revealed a negative correlation of BMD (T-score) with age and a positive correlation with BMD and Kellgren score (p < 0.05). Even after multiple adjustment for confounders lumbar spine BMD is significantly higher in throwers, pole vaulters, and long- and triple jumpers than in marathon athletes. Different types of mechanical loading caused by sporting activities seem to influence the BMD of the lumbar spine, even if different body constitutions (i.e. BMI) and age, training history, and degenerative changes in the lumbar spine of former throwers, jumpers, and endurance athletes are taken into consideration.